The impact of chatbots on emotional intelligence in AI-assisted EFL writing - Kazazoglu, Semin; Turun Özel, Gamze (Frontiers in Education, 2025)
IntroductionThe increasing integration of technology in language teaching has led to a significant focus on chatbots, which utilize various artificial intelligence models tailored to English as a Foreign Language education. While the effectiveness of chatbots in enhancing language skills is well documented, their influence on emotional intelligence (EI) has not been thoroughly examined. This study explores the impact of chatbot use on EI among sophomore pre-service English language teachers in Istanbul, Türkiye.MethodsUtilizing the Turkish-adapted version of Bar-On's Emotional Quotient Inventory (EQ-I), quantitative methods were employed to examine the relationship between frequent interactions with ChatGPT and EI levels.ResultsThe results indicate a moderate, statistically significant negative correlation, suggesting that increased use of ChatGPT may be associated with lower EI. A slight improvement was noted in adaptability, though this trend should be interpreted cautiously.Discussion and conclusionThe study highlights the complex and context-dependent role of chatbots in shaping emotional competencies in language education and points to the need for further investigation. The results contribute to ongoing discussions on AI in educational settings by underscoring the importance of carefully balancing potential benefits with challenges to support both language proficiency and emotional development.